NANOEMULSION AND METHOD FOR PREPARATION THEREOF, AND HIGH-TEMPERATURE-RESISTANT, HIGH-DENSITY, OIL-BASED WELL COMPLETION FLUID AND APPLICATION THEREOF - LIU, Rentong; ZHANG, Jiaqi; CHENG, Rongchao; CUI, Xiaobo; GAO, Shan; WANG, Jianhua; YAN, Lili; NI, Xiaoxiao; LIU, Fengbao; YANG, Haijun (2023)
Provided by the present invention are a nanoemulsion and method for preparation thereof, and a high-temperature-resistant, high-density, oil-based well completion fluid and application thereof. The nanoemulsion comprises a lipophilic alkenyl monomer, a hydrophilic alkenyl monomer, an emulsifier, a cross-linking agent, and water. The high-temperature-resistant high-density oil-based completion fluid comprises a base oil, a main emulsifier, an auxiliary emulsifier, an aqueous solution of salt, organic soil, an alkalinity regulator, a filtration loss reducer, a stabilizer, and a weighting material; the stabilizer comprises the described nanoemulsion. La présente invention concerne une nanoémulsion et un procédé de préparation de cette dernière, et un fluide de complétion de puits à base d'huile, haute densité, résistant aux hautes températures, et leur application. La nanoémulsion comprend un monomère alcénylique lipophile, un monomère alcénylique hydrophile, un émulsifiant, un agent de réticulation et de l'eau.